4 - Engendering Mauritian History: The Hidden Controversies over Female Suffrage - Ramola Ramtohul, (Afrika Zamani, 2022)
This article examines the controversy over female suffrage in Mauritius at the time of British colonial rule. Mauritius presents itself as an interesting historical paradox on the timing and form of women’s enfranchisement. This issue has been marginalised by male dominated historical accounts. Drawing from the constitutional debates of the 1940s that took place in parliament and were reproduced in verbatim in the press, the paper examines the manner in which female suffrage was attained in Mauritius. It argues that despite the strongly entrenched patriarchal culture in the island, the social divisions (ethnic and class) in the population had a major bearing on the debates over female suffrage, which were eventually beneficial to a class of women. The study reveals how the strength and domination of class and ethnic lobbies clearly marginalised women’s interests and silenced women. This article thus attempts to undo some of the male bias in Mauritian socio-political history.